2021
DOI: 10.13189/ujaf.2021.090108
|View full text |Cite
|
Sign up to set email alerts
|

Energy Consumption and Sectorial Value Addition on Economic Growth in Nigeria

Abstract: This study investigates the co-integrating and causal link between energy consumption and economic growth in three economic sectors of agriculture, manufacturing, and service sectors in Nigeria. Through the multivariate framework and quarterly data from 2000Q 1 -2018Q 4 . The ARDL bounds test approach, and Error Correction Model are the key techniques of analysis, and the Clemente-Montanes-Reyes unit root approach for structural breaks in the series. Findings revealed estimated billing system, and energy deman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The result established a unidirectional causal relationship running from energy consumption LEC to electricity distribution losses LEDL while a bidirectional relationship was found between electricity intensity level LEIL causing LEPC electric power consumption and carbon emission LCO 2 . Our result is consistent with (Samuel et al 2021) for the case of Nigeria and (Ouédraogo, 2010) Burkina Faso. However, it is imperative for policy and decision makers to note that energy intensity level of the studied region tends low indicating lower cost of conversion to output or GDP ratio as reflected on our estimates.…”
Section: Discussionsupporting
confidence: 91%
“…The result established a unidirectional causal relationship running from energy consumption LEC to electricity distribution losses LEDL while a bidirectional relationship was found between electricity intensity level LEIL causing LEPC electric power consumption and carbon emission LCO 2 . Our result is consistent with (Samuel et al 2021) for the case of Nigeria and (Ouédraogo, 2010) Burkina Faso. However, it is imperative for policy and decision makers to note that energy intensity level of the studied region tends low indicating lower cost of conversion to output or GDP ratio as reflected on our estimates.…”
Section: Discussionsupporting
confidence: 91%
“…Prior empirical data has shown that special prices react nonlinearly to price changes and that bidirectional causality pricing exists [44], [45]. This link was confirmed further [46]- [48].…”
Section: Iiliterature Reviewmentioning
confidence: 60%
“…Udo, Idamoyibo, Inim, Akpan, and Ndubuaku [11] investigated the co-integration and causal connexion between energy consumption and economic growth in Nigeria's agricultural, manufacturing, and service sectors. Owing to quarterly data spanning from 2000Q1 to 2018Q4, the analysis revealed a combination of outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%